2000
DOI: 10.1159/000047210
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Dimorphic Expression of Glutamate Decarboxylase mRNA in the Hypothalamus of the Deep Sea Armed Grenadier, <i>Coryphaenoides (Nematonurus) armatus</i>

Abstract: Glutamate decarboxylase (GAD), is a key enzyme in the central nervous system (CNS) that synthesizes the inhibitory neurotransmitter gamma-aminobutyric acid (GABA) from glutamate. Our previous phylogenetic studies on the evolution of this enzyme indicates that there are at least two distinct forms: GAD65 and GAD67. They are the products of separate genes and probably derive from a common ancestral GAD gene following gene duplication prior to the emergence of the teleosts more than 200 Myr ago. Furthermore, a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 30 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…The authors concluded that GAD mRNA are translated efficiently into enzymatically active GAD which produces GABA, and that the pattern of GAD expression is consistent with the notion that GAD and its product, GABA, play a signaling role during development. In another study, utilizing the polymerase chain reaction, it was shown that the hypothalamic expression of GAD 65 was significantly greater in the male deep sea armed grenadier (Coryphaenoides (Nematonurus) armatus) than in the female indicating that the synthesis of GABA is sexually dimorphic in this species [Trudeau et al, 2000b]. In the present study we demonstrated, by in situ hybridization, that in larval lamprey, both GABA and GAD were present in the same population of cells.…”
Section: Discussionsupporting
confidence: 64%
“…The authors concluded that GAD mRNA are translated efficiently into enzymatically active GAD which produces GABA, and that the pattern of GAD expression is consistent with the notion that GAD and its product, GABA, play a signaling role during development. In another study, utilizing the polymerase chain reaction, it was shown that the hypothalamic expression of GAD 65 was significantly greater in the male deep sea armed grenadier (Coryphaenoides (Nematonurus) armatus) than in the female indicating that the synthesis of GABA is sexually dimorphic in this species [Trudeau et al, 2000b]. In the present study we demonstrated, by in situ hybridization, that in larval lamprey, both GABA and GAD were present in the same population of cells.…”
Section: Discussionsupporting
confidence: 64%
“…In the deep-sea fish in which gad3 was first described, the armed grenadier, Coryphaenoides (Nematonurus ) armatus, gad2 mRNA levels were found to be expressed in the brain in a sexually dimorphic manner, i.e. higher in male hypothalamus than in female, but no differences were found in gad3 levels 35 . In the goldfish, however, gad3 mRNA levels in the telencephalon were highest in sexually mature fish of both sexes during the breeding period 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Transcript DNA sequences for elephant shark were retrieved from the elephant shark Ensembl server. Transcript cDNA sequences for grenadier were retrieved from NCBI 15 35 . The spotted gar genome shares extensive similarity with both tetrapod and teleost genomes, so we chose to focus on this species for sequence alignment, phylogenetics, and intron/exon structure comparisons 30 .…”
Section: Methodsmentioning
confidence: 99%
“…It is known that there are three different isoforms of the gene in vertebrates (Grone & Maruska 2016). In fishes, some studies have been directed at the deep sea armed grenadier Coryphaenoides (Nematonurus) armatus (Trudeau et al 2000), goldfish (Lariviere et al 2002), zebrafish (Mueller & Guo 2009), and detected by RNAseq in gulf pipefish Syngnathus scovelli (Beal et al 2018). Hence, in zebrafish, Cocco et al (2017) studied gad localization in different brain regions and found three different paralogs, of which two resemble the gad1 paralog of mammals and the third one the gad2.…”
Section: Glutamate Decarboxylase (Gad)mentioning
confidence: 99%